انعكاسات القوانين الداخلية والاتفاقيات الدولية على مكانة المرأة في المجتمع - بن رية سارة (جامعة المسيلة, 2021)
ظل موضوع المرأة ومكانتها محلاً للجدل في معظم المجتمعات والشرائع السماوية على مر تاريخ الإنسانية، وكنتيجة للتغيرات السريعة التي شهدتها العصور في جميع مناحي الحياة أثرت القوانين الداخلية والاتفاقيات الدولية على مكانة المرأة، إذ سعت هاته الأخيرة إلى تكريس حقوق المرأة وإرساء مبدأ المساواة بين الجميع دون أي تمييز لا على أساس العرق أو الدين أو اللغة أو اللون أو الجنس. مما أدت هذه التطورات والاعتداءات الصارخة للاتفاقيات الدولية إلى تغيير مكانة المرأة والمساس بصورتها النمطية. Summary: The issue of women and their status has been a subject of controversy in most societies and divine laws throughout human history, and as a result of the rapid changes that the ages have witnessed in all walks of life, domestic laws and international conventions have affected the status of women, as the latter sought to enshrine women’s rights and establish the principle of equality among all without any Discrimination not on the basis of race, religion, language, color or gender. Which led to these developments and flagrant attacks on international conventions to change the status of women and prejudice their stereotyped image. 07:40
Keywords: مكانة المرأة -القوانيين الداخلية